PENGARUH BOARD CHARACTERISTICS TERHADAP CORPORATE RISK DISCLOSURE YANG DIMODERASI OLEH FAMILY OWNERSHIP - Joshua Suherman; Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims at how the role of the board characteristics on corporate risk disclosure, and the moderation effect of family ownership toward the relation of board characteristics to corporate risk disclosure on consumer goods industry listed on the Indonesia Stock Exchange during 2016-2018. Sample was selected using purposive sampling method and the valid data was 39 companies. Data processing techniques using multiple regression analysis what helped by Eviews version 13 and Microsoft Excel 2020. The results of this study indicate that board characteristics which consist of board size, board meeting, CEO duality, and board expertise do not have a significant influence on corporate risk disclosure, meanwhile family ownership has a significant influence to moderate the relation of board size, board meeting, and CEO duality towards corporate risk disclosure. Family ownership does not moderate the relation of board expertise towards corporate risk disclosure. The implication of this study is the need to increase the role of the board members to influence the corporate risk disclosure which will be needed by investors and potential investors as well.